Creative People as a New Source of Competitive Advantage in Creative Industry - Eriana Astuty; Suryana Suryana (Sebelas Maret Business Review, 2017)
Today’s development of creative industries in the economy of Indonesia has shown a significant improvement. Creative industries have contributed in improving the growth of Gross Domestic Product (GDP), employment opportunities, and national industries. Unfortunately, those improvements are not in line with their internal developments. The purpose of this study is to find the answer of the gap phenomenon that occured. It is found that only three sub-sectors out of 15 have positive contributions as mentioned above. They include craft, fashion, and culinary. Primary data were obtained through a questionnaire survey and observation carried out in  batik and woven-fabric business units in 6 provinces in Indonesia. By conducting survey as the research methodology in which the data were evaluated using statistic tools such as SPSS and AMOS 20, it is found that creative people as renewable resources have been able to improve Indonesia competitive advantage in crafts industries by reflecting local culture and heritage through creativity on various innovations.